Efecto tóxico del DDT, dordano yagua de la presa Ignacio Ramírez (México), sobre Daphnia magna (Crustacea: Daphnidae) - Martínez-Tabche, Laura (1999)
Chlorodiphenylnitrichloroethane (DDT) and chlordane (CLO) are currently used in Mexico to control malaria and tennites. From 1990 lo 1996 a total of 27 ton of DDT and 508 of CLO were imported. We, establish a methodology to detennine their environmental impaet in a Mexican dam (Ignacio Ramírez). The toxie effeel of DDT and CLO were evaluated on the o-demethylase (OD) and acethycholinesterase activities (AchA) of ¡he c\adoceran Daphnia magna exposed to different concentrations of the insecticides solved in water from three sÍles. Their effeet on the AchA and OD aetivities, and so the CL50 were used as exposure bioindicalors lO determine the more polluted sites. The physicochemical characteristics of water and the biodiversity of the dam test siteswere considered. The station near the floodgate has toxicity potential because enzimatic activities were moditied. We suggest the use of AchAand OD activities measure in Ihecladoceran to evaluate the toxicity of a water body polluted by organochlorate insecticides.